The mediating role of halal supply chain integrity in enhancing performance for halal herbal-based food SMEs - Rajendran, Salini Devi; Kamarulzaman, Nitty Hirawaty; Abd Rahman, Azmawani (Emerald Publishing, 2024)
Purpose – This paper aims to examine the influence of supply chain management by assessing the relationship between internal and external integration and small and medium enterprises (SMEs) owners’ Islamic practices in enhancing halal supply chain integrity (HSCI) and SMEs’ performance. Design/methodology/approach – A total of 176 SMEs were surveyed using a self-administered questionnaire. The sample was selected using convenience sampling from two major halal exhibition events in Malaysia. Structural equation modeling (SEM) was used to analyze the data and test the hypotheses. Findings – The findings showed that supply chain integration (SCI), Islamic human capital and HSCI have a significant relationship with SMEs’ performance. It was also found that HSCI mediated the relationship between both SCI and Islamic human capital and SMEs’ performance. Practical implications – SME owners or managers should be committed to developing the internal processes within the organization and strategizing to link these processes with the external processes to obtain the full benefits of integration. Furthermore, as the upper management, owners and managers must understand the supply chain challenges, priorities and practices thoroughly, as they are responsible for Islamic business ethics. They should work to provide support to increase religious orientation in the SMEs, as this would likely enhance all other factors.